2011
DOI: 10.3102/0002831210365008
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-Child Relationship and Behavior Problem Trajectories in Elementary School

Abstract: The present study examined associations between the quality of teacher-child relationships and behavior problems among elementary school students using data from the NICHD Study of Early Child Care and Youth Development, a study of 1,364 children from birth through adolescence. There were two main findings. First, high-quality teacher-child relationships predicted low levels of externalizing behaviors. Second, high-quality relationships acted as protective factors, helping to prevent children with high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
237
5
23

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(279 citation statements)
references
References 126 publications
(168 reference statements)
14
237
5
23
Order By: Relevance
“…The use of positive behavior support decreases the need for more intrusive or aversive intervention (i.e., punishment or suspension) that is harmful to teacher-student relationship. Because boys tend to display more behavior problems than girls in school, positive behavior support will be particularly beneficial to boys (Hughes, Cavell, & Willson, 2001;O'Connor, Dearing, & Collins, 2011). It can help them maintain better relationships with their teachers and feel more supported by their teachers.…”
Section: Implications For the Work Of School Psychologistsmentioning
confidence: 99%
“…The use of positive behavior support decreases the need for more intrusive or aversive intervention (i.e., punishment or suspension) that is harmful to teacher-student relationship. Because boys tend to display more behavior problems than girls in school, positive behavior support will be particularly beneficial to boys (Hughes, Cavell, & Willson, 2001;O'Connor, Dearing, & Collins, 2011). It can help them maintain better relationships with their teachers and feel more supported by their teachers.…”
Section: Implications For the Work Of School Psychologistsmentioning
confidence: 99%
“…Longitudinal studies of elementary school children have found that positive trajectories of child-teacher relationship quality (characterized by children experiencing high closeness and less conflict over time) are significantly associated with better academic outcomes [6], [10], and better mental health outcomes [18], [25], [26]. For example, [25] used person-centered longitudinal analyses to identify different trajectory groups on teacher-child relational closeness and conflict in the first 5 years of school.…”
Section: B Child-teacher Relationship Trajectoriesmentioning
confidence: 99%
“…Tal aspecto parecia também ficar evidenciado na estrutura física, com portões de ferro sempre fechados. Na presente pesquisa, além de atitudes agressivas, encontrou-se também o distanciamento afetivo e a falta de espontaneidade, configurando uma falta importante de um aspecto considerado favorável, benéfico, para a relação professor-aluno e para o aprendizado e desenvolvimento emocional da criança (CURBY; RIMM-KAUFMAN; PONITZ, 2009;DOUMEN et al, 2011;KIM, 2008;LEITE, 2008;MACARINI;MARTINS;VIEIRA, 2009;MELO;SILVARES, 2010;O´CONNOR, 2011;RIBEIRO, 2010;RUDASSIL, 2011;TAVARES,2005). Além disso as professoras expressaram sentir-se despreparadas para lidar com aspectos afetivo-comportamentais de seus alunos, bem como terem dúvidas em relação ao seu papel nesta área da educação, que não a área pedagógica, corroborando com o exposto por Araújo, Sperb (2009) e Ribeiro (2010.…”
Section: Discussionunclassified
“…(CURBY; RIMM-KAUFMAN; PONITZ, 2009;DOUMEN et al, 2011;MARTURANO;TRIVELLATO-FERREIRA;GARDINAL, 2009;O´CONNOR, 2011;RUDASILL, 2011;SINK;EDWARDS;WEIR, 2007). Fazendo um paralelo com os dados da pesquisa, pode-se pensar que também o professor experimenta ansiedade e medo relacionados ao desafio de alfabetizar, de ensinar, no primeiro ano de Ensino Fundamental.…”
Section: Discussionunclassified
See 1 more Smart Citation